1963
DOI: 10.1111/j.1570-7458.1963.tb00619.x
|View full text |Cite
|
Sign up to set email alerts
|

DISPERSAL OF THE GLASSHOUSE RED SPIDER MITETETRANYCHUS URTICAEKOCH (ACARINA, TETRANYCHIDAE)

Abstract: Under glass Tetranychus urticae Koch spreads by (a) migration of teneral females to ovi‐position sites (b) migration of mites from heavily infested plants by falling without the usual silken parachutes normally used by Tetranychid mites and (c) movement over the soil surface in accordance with the plane of polarized light. It is postulated that the effect of this combination of dispersal mechanisms is to restrict mite populations to one portion of a glasshouse from season to season with relatively slow lateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
1

Year Published

1981
1981
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(63 citation statements)
references
References 3 publications
3
58
1
Order By: Relevance
“…To our knowledge, ours is the first report of a lack of response to specific wavelengths during diapause. Although Hussey and Parr (Hussey and Parr, 1963) showed light avoidance in diapausing females of T. urticae, the light source (which they did not describe) would have included some UV if they used sunlight or fluorescent tubes; thus, avoidance of UV would have been induced, as we observed here (Fig.2D). Mori (Mori, 1962) showed that T. urticae females collected in late October (autumn) were less sensitive to light than those collected in summer in Sapporo, Japan (43°N).…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…To our knowledge, ours is the first report of a lack of response to specific wavelengths during diapause. Although Hussey and Parr (Hussey and Parr, 1963) showed light avoidance in diapausing females of T. urticae, the light source (which they did not describe) would have included some UV if they used sunlight or fluorescent tubes; thus, avoidance of UV would have been induced, as we observed here (Fig.2D). Mori (Mori, 1962) showed that T. urticae females collected in late October (autumn) were less sensitive to light than those collected in summer in Sapporo, Japan (43°N).…”
Section: Discussionsupporting
confidence: 57%
“…Hussey and Parr (Hussey and Parr, 1963) showed that the avoidance of light was induced upon diapause in T. urticae, although they did not present light spectra. Diapause is defined as a hormonally mediated metabolic arrest with an increase in resistance to environmental stresses, a change in behaviour, and suppression of morphogenesis (Tauber and Tauber, 1981).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, mated females appear to incur cost due to the presence of males. In T. urticae, mated females disperse from the natal colony and found a new colony (Hussey and Parr 1963) to avoid food deterioration (Kondo and Takafuji 1985;Oku et al 2002). Mated females of T. urticae may also disperse to avoid costs of the disturbance by males.…”
Section: Discussionmentioning
confidence: 99%
“…In nature, the environment experienced by T. urticae is normally highly variable [50]. Tetranychus urticae can exploit and destroy their resources very quickly, and because many of their host plants are agricultural, the constant harvesting and regrowth imply a constantly changing habitat [51]. A second requirement is that the costs of transmitting the non-genetic information from mother to offspring must be low.…”
Section: Discussionmentioning
confidence: 99%